Home education: The social motivation - Christian W. Beck (International Electronic Journal of Elementary Education, 2010)
Data from a Norwegian survey show correlation between a student’s socially related problems at school and the parent’s social motivation for home education. I argue that more time spent at school by a student could result in more socially related problems at school, which can explain an increase in social motivation for home education.